2017
DOI: 10.1515/folmed-2017-0004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Training at Lactate Threshold Intensity on Maximal Time to Exhaustion, Depression and Anxiety Behaviour of Spontaneously Hypertensive Rats after Kainate-Induced Status Epilepticus

Abstract: Citation: Georgieva KN, Hadjieva MS, Doseva MS, Terzieva DD, Georgiev NG, Andreev GG, Tchekalarova JD. Eff ect of training at lactate threshold intensity on maximal time to exhaustion, depression and anxiety behaviour of spontaneously hypertensive rats after kainate-induced status epilepticus.Folia Medica 2017;59(1): 91-97. doi: 10.1515/folmed-2017-0004 Aim: The objective of the present study was to investigate the eff ect of treadmill training at lactate threshold intensity on maximum time to exhaustion (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…This notion has also been supported by various behavioral studies in animals, which reported training protocols that induced an anxiolytic effect in rodents (Ke et al, 2011;Tchekalarova et al, 2015;Ghodrati-Jaldbakhan et al, 2017). On the other hand, some studies failed to demonstrate the anxiolytic effect of exercise training (Chaouloff, 1994;Hoffman et al, 2015;Georgieva et al, 2017), as well as Fuss et al (2010a;2010b), which reported a contrary result suggesting an anxiogenic effect of exercise training. These contradictory results primarily originate from differences in type, intensity, and duration of exercise between protocols.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…This notion has also been supported by various behavioral studies in animals, which reported training protocols that induced an anxiolytic effect in rodents (Ke et al, 2011;Tchekalarova et al, 2015;Ghodrati-Jaldbakhan et al, 2017). On the other hand, some studies failed to demonstrate the anxiolytic effect of exercise training (Chaouloff, 1994;Hoffman et al, 2015;Georgieva et al, 2017), as well as Fuss et al (2010a;2010b), which reported a contrary result suggesting an anxiogenic effect of exercise training. These contradictory results primarily originate from differences in type, intensity, and duration of exercise between protocols.…”
Section: Introductionmentioning
confidence: 75%
“…In the literature, there are contradictory results regarding the effect of exercise. Some authors reported an anxiolytic effect with training (Ke et al, 2011;Tchekalarova et al, 2015;Ghodrati-Jaldbakhan et al, 2017), and some observed no differences (Chaouloff, 1994;Hoffman et al, 2015;Georgieva et al, 2017). Then, others reported an exercise-induced anxiogenic effect (Fuss et al, 2010a;2010b).…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that aerobic training contributed to a higher resistance to KA-induced SE in SHRs through increasing the threshold for SE onset during repetitive injection of low subconvulsive doses of KA. It may be inferred that improved physical working capacity (Georgieva et al, 2015) as well as decreased systolic and mean arterial pressure in SHRs resulting from the exercise program can contribute to the positive effect of endurance training on the neurotoxic effect of KA.…”
Section: Discussionmentioning
confidence: 99%
“…Epilepsy itself and most of the antiepileptic medications impair the cognitive functions [51], which requires the search for methods that complement the basic therapy to reduce cognitive deficits. Our previous experimental studies have shown that the regular physical exercise reduces the cognitive deficit from the application of antiepileptic medications and suppresses depression and anxiety behavior in epilepsy [44,51,52].…”
Section: Mental Healthmentioning
confidence: 99%
“…A number of clinical and experimental studies evidence that the recreation physical exercise of the aerobic type can be used as a prevention or drug-free therapy for hypertension, as it has a hypotensive effect and favorably affects some of the cardiovascular risk factors (dyslipidemia, insulin resistance, obesity, etc. ), resulting in a reduced risk of cardiovascular morbidity and mortality [33,34]. One of the largest meta-analyses conducted so far shows that aerobic exercise in hypertensives reduces systolic pressure by about 5-10 mmHg but has almost no effect on diastolic arterial blood pressure [35].…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%